2020
DOI: 10.3389/fimmu.2020.00839
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine 2,3-Dioxygenase 2 Immunohistochemical Expression in Resected Human Non-small Cell Lung Cancer: A Potential New Prognostic Tool

Abstract: Indoleamine 2,3-dioxygenase 2 (IDO2) is an analog of the tryptophan degrading and immunomodulating enzyme indoleamine 2,3-dioxygenase 1 (IDO1). Although the role of IDO1 is largely understood, the function of IDO2 is not yet well-elucidated. IDO2 overexpression was documented in some human tumors, but the linkage between IDO2 expression and cancer progression is still unclear, in particular in non-small cell lung cancer (NSCLC). Immunohistochemical expression and cellular localization of IDO2 was evaluated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
46
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(49 citation statements)
references
References 63 publications
3
46
0
Order By: Relevance
“…Among these, IDO-1 was evaluated as a further target for immunotherapeutic intervention by the evidence reported in some studies showing its pro-tumorigenic effect [46]. Regarding the expression of IDO-1 and IDO-2, several studies show that their role can influence tumor progression [47]. In particular, the study by Lindström, V, et al showed that increased IDO-1 activity in patients with chronic lymphatic leukemia may affect disease progression [48].…”
Section: Discussionmentioning
confidence: 99%
“…Among these, IDO-1 was evaluated as a further target for immunotherapeutic intervention by the evidence reported in some studies showing its pro-tumorigenic effect [46]. Regarding the expression of IDO-1 and IDO-2, several studies show that their role can influence tumor progression [47]. In particular, the study by Lindström, V, et al showed that increased IDO-1 activity in patients with chronic lymphatic leukemia may affect disease progression [48].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, human gastric, colorectal, and renal carcinomas have been found to constitutively express both IDO1 and IDO2 (24), and the same has been observed in brain tumors (25). Interestingly, IDO2 is particularly overexpressed in pancreatic ductal adenocarcinoma (PDAC) (26) and non-small-cell lung cancer (NSCLC) (27).…”
Section: Ido2 Expression and Function In Tumors: A Matter Of Geneticsmentioning
confidence: 95%
“…In a recent study with 191 NSCLC patients, IDO2 was highly expressed in 84% of samples and its expression was strictly related to high PD-L1 levels (27). Perhaps most importantly, a significant correlation between IDO2 high expression and poor NSCLC prognosis was detected (27). Intriguingly, IDO2 expression was mainly associated with the basolateral side of the tumor cell membrane, and only few cells stained for IDO2 in the cytosol or nucleus.…”
Section: Ido2 In Human Non-small Cell Lung Cancer (Nsclc)mentioning
confidence: 98%
See 1 more Smart Citation
“…Other immuneindependent effects caused by PD-L1 include the activation of mTORC1 and Ras/ERK and signaling cascades, with the following sustained growth of melanoma and ovarian cancer cells and enhanced EMT in glioblastoma multiforme, respectively [96,97]. Moreover, Mandarano et al showed a correlation between upregulated IDO2 and PD-L1 levels, which indicates the existence of a link between IDO2 activity and enhanced cancerogenesis in a PD-L1-dependent manner [98]. Besides affecting PD-L1 expression, NAD + contributes to stem cell proliferation and pluripotency [99].…”
Section: Tdo2 Ido2 and Their Role In Cancer Developmentmentioning
confidence: 99%